Moral Problems and Efforts to Overcome Them In The Fisherman Community Environment of Nibung Hangus District, Batu Bara - Wirdani, Ika; Dahlan, Zaini; Asari, Hasan (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
This research examines various moral problems among teenagers in Ujung Kubu Village, Nibung Hangus Sub-district, Batu Bara Regency. This research aims to identify and analyze the factors that influence adolescents' moral behavior and the efforts made by fishermen's families to overcome these problems. A qualitative approach with a case study was used as the primary method. Data collection techniques included passive participatory observation, in-depth interviews with key informants, and document study. Data analysis was conducted using descriptive analysis techniques, narrative compilation, and verification through triangulation and member checks to ensure the accuracy and consistency of the findings. The research findings show that behavior against parents, abusive speech, fighting among friends, and often leaving the house in the middle of the night are serious moral problems among adolescents in this village. Factors influencing these problems include the role of parents, the influence of the peer environment, and the lack of consistent religious education. Parents face challenges in implementing moral education amid negative environmental influences. Family efforts include open communication, setting clear rules, and limiting the peer environment, although there are limitations in fully controlling children's behavior. This study reinforces previous theories about the importance of family and environment in adolescent moral formation and provides new insights into the complexity of moral issues in fishing communities. A more adaptive and responsive approach is needed to create an environment conducive to healthy and responsible adolescent development.